Análise da variabilidade temporal de base na propagação da onda cinemática em um rio - Castro, Maria Patrícia Sales (2017)
The Kinematic Wave was applied in a natural river, to study the propagation of a flood wave in this body of water. This research aims to analyze the temporal variability of base kinematic wave routing in a river, checking how these can influence the risk of flooding. Those models are getting from the Dynamic Wave Model, starting from simplifications in Saint Venant's Equations, where some terms are despised. In the process of solution of the differential equations, concerning with the model, the Finite Difference Method was used, and the explicit approach was applied for the kinematic wave. For this research, a computational program, in PYTHON language, it was developed. It allowed that some simulations could be made for different sceneries, normally, found in the natural rivers. From the results generated can be observed that the roughness coefficient influences the time base of wave propagation in time, making this model a viable tool for forecasting flooding in susceptible areas.